2020
DOI: 10.1063/5.0033681
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of elliptical planar Hall effect magnetometers

Abstract: We fabricate elliptical planar Hall effect magnetometers with Permalloy thickness ranging between 25 and 200 nm. We study the thickness dependence of their equivalent magnetic noise by examining the effect of the layer thickness on the signal and noise including Joule heating contributions. Sensors with a thickness of 50 nm achieve equivalent magnetic noise as low as ∼24 pT/√ Hz at 50 Hz and ∼36 pT/√ Hz at 10 Hz, which are the best reported values for any type of magnetic sensor of similar or smaller size. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Our data reveal that it is more desirable to use a bilayer sensor for the larger dynamic range of ~10 mT, but a tri-layer sensor can be used for higher resolution. In order to improve the sensor detection limit further, tri-mPHMR sensors (>5 rings) and an adjustable electronic circuit with some advanced noise reduction technologies [ 15 , 16 , 21 ] can be designed next. PHMR sensors are therefore general-purpose high-performance magnetometers that can potentially satisfy most kinds of requirements for a wide range of applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data reveal that it is more desirable to use a bilayer sensor for the larger dynamic range of ~10 mT, but a tri-layer sensor can be used for higher resolution. In order to improve the sensor detection limit further, tri-mPHMR sensors (>5 rings) and an adjustable electronic circuit with some advanced noise reduction technologies [ 15 , 16 , 21 ] can be designed next. PHMR sensors are therefore general-purpose high-performance magnetometers that can potentially satisfy most kinds of requirements for a wide range of applications.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely-low magnetic field sensing in the low-frequency range is an important task for a wide range of application areas such as magnetic random access memory (MRAM) [ 1 ], neuromorphic computing [ 2 ], magnetic communication [ 3 , 4 ], noninvasive biomedical diagnosis [ 5 , 6 , 7 , 8 ], nondestructive materials evaluation [ 9 ], human–machine interaction [ 10 , 11 ], robotics [ 12 ], and automotive or consumer-based industrials [ 13 ]. Most of these applications demand miniaturization, low-cost fabrication, high thermal stability, flexibility in usage, and robustness in a harsh environment with a very high sensor resolution [ 14 , 15 , 16 , 17 ]. In this perspective, many researchers have been involved in the development of an ultra-sensitive magnetic sensor over the past ten years, and it has been found that magnetoresistive (MR) sensor is always one of the best choices due to its high scalability and inherent capability to install ROIC (readout integration circuit) and also due to its excellent integration compatibility with CMOS (complementary metal-oxide-semiconductor) MEMS (micro-electro-mechanical systems) devices [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A constant current is driven along the ellipse’s long axis, and the transverse voltage is measured across the ellipse’s short axis to detect the magnetic field. The EPHE sensor is attractive compared with other magnetoresistive sensors due to its low-temperature dependence [ 38 ], simple fabrication, and high resolution [ 17 , 21 , 22 , 37 ]. Grosz et al reported PHE sensors with an equivalent magnetic noise or resolution of ~200 pT/√Hz [ 21 ], and the noise can be reduced to ~5 pT/√Hz by adding a magnetic flux concentrator [ 11 , 37 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the Hall effect also exists in metals. The low resistance of metals could increase uniformity of the current density and reduce dependence of linearity on bias current [ 9 , 10 ]. However, the transverse voltage is too small to have any practical application [ 11 ].…”
Section: Introductionmentioning
confidence: 99%